Five-year practice of laser vision correction using the ReLEx smile technique - Zavgorodnyaya, N. G.; Poplavska, I. O.; Kostrovska, K. O.; Завгородня, Наталія Григорівна; Поплавська, Ірина Олександрівна; Костровська, Катерина Олегівна (My University, 2025)
To analyze the outcomes of laser vision correction using the ReLEx SMILE technique in patients with myopia and complex myopic astigmatism.
Keywords: тези доповідей